Investigation of the potential suitable areas for pineapple plantation using GIS / Hafiza Yahaya - Yahaya, Hafiza (2010)
Geographic information System(GIS) becomes more popular and important in many application such as plantation, development and etc. This GIS is used to produce updated information, faster and help in decision making. GIS application in analyze the suitable to crop the fruit, that is constitute a research model to evaluate system in future. In our final project, GIS is a tool that help in make our analysis and also help in make a decision making to produce a map that is most suitable to plant Pineapple (Comulus Ananas) at Pontian Johor. The criteria to plant the Pineapple (Comulus Ananas) is depend on their land category and also terrain (contour) of the location that is refer to Soil-Crop Suitability classification for Peninsular Malaysia system. The suitable plantation analysis involves collection of spatial data, attribute data and manipulation process of both data. Data that are completed with manipulation process will be use in analysis process that use the GIS software. This project is focus on producing a map for the most suitable plantation of Pineapple (Comulus Ananas) where it depends on some criteria. The criteria are Slope of the location, Soil Type, Temperature, Rainfall and also Land use of site area.From this research product can help the decision maker to make their solution in planning to plant Pineapple(Comulus Ananas) and also can manage their planning with more effectie and succesfull.